Study of novel lithium salt-based, plasticized polymer electrolytes - Silva, Maria Manuela (2002)
The results of a preliminary investigation of a series of polymer electrolytes based on a novel polymer host, poly(trimethylene carbonate) or p(TMC), with lithium triflate or lithium perchlorate and various plasticizing additives, are described in this presentation. Electrolytes with lithium salt compositions of about n = 10 (where n represents the molar ratio of (O=COCH2CH2CH2O) units per lithium ion) and additive compositions between 5 and 15 wt% (with respect to p(TMC)), were prepared by co-dissolution of salt and polymer in anhydrous solvent with a controlled amount of additive. The homogeneous solutions obtained were evaporated within a preparative glovebox and under a dry argon atmosphere to form thin films of electrolyte. The solvent-free electrolyte films produced were characterized by measurements of total ionic conductivity, differential scanning calorimetry and thermogravimetry. In general the triflate-based electrolytes were found to show moderate ionic conductivity and good thermal stability while perchlorate-based electrolytes showed higher levels of conductivity but lower thermal stability. Electrolytes based on this host polymer, with both lithium salts, were obtained as very flexible, transparent, completely amorphous films.